ChatGPT : Transforming Face of Dentistry (Academia Journal of Medicine, 2023)
In recent years, artificial intelligence (AI) has found its  way into numerous industries, transforming the way  we work and live. Dentistry is no exception, as AI powered technologies are revolutionizing the field,  making it more efficient and enhancing patient care.  One such breakthrough is the application of ChatGPT  in dentistry. ChatGPT, powered by OpenAI, is a  powerful language model that can comprehend and  generate human-like responses, enabling dentists and  their teams to leverage its potential in a multitude of  ways. This article explores how ChatGPT is being  applied in dentistry and the benefits it brings to both  professionals and patients.
Keywords: ChatGPT; AI; Dentistry